PENGARUH MOTIVASI, KOMPETENSI DAN KOMITMEN TERHADAP KEPUASAN KERJA KARYAWAN PT. EKA LORENA TRANSPORT DI BOGOR JAWA BARAT - Lalu Mahdi; Robi Wijaya (Jurnal Satya Mandiri Manajemen dan Bisnis, 2017)
This research aims to find out the influence of motivation, compensation and commitment to the job saticfaction of the employees of PT. Eka sari Lorena Transport in Bogor. Based on the test result together to show a significant result where the result of 3,649 Fhit, From the result the state Fhit> Ftab or 3,649> 2,66 then the hypotesis Ho was rejected and Ha accepted. Thus concluded there is a positive and significant impact between the motivation, compensation and commitmen together againt job satifaction in PT.Eka Sari Lorena Transport di Bogor.